2020
DOI: 10.1186/s12916-020-01740-5
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of the centrality hypothesis in cross-sectional between-subject networks of psychopathology

Abstract: Background In the network approach to psychopathology, psychiatric disorders are considered networks of causally active symptoms (nodes), with node centrality hypothesized to reflect symptoms’ causal influence within a network. Accordingly, centrality measures have been used in numerous network-based cross-sectional studies to identify specific treatment targets, based on the assumption that deactivating highly central nodes would proliferate to other nodes in the network, thereby collapsing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 88 publications
(180 reference statements)
0
53
0
Order By: Relevance
“…However, this measure does not capture indirect associations between nodes. Empirically, the implication of network theory that strength centrality in cross-sectional networks predicts the strength of the association between a symptom's change and the change in the severity of all other symptoms in the network from pre-to post-treatment has received mixed support (Spiller et al, 2020). A fourth limitation is the cross-sectional design, which impairs the ability to draw conclusions about temporal precedence and greater insight into causal direction of the relationships obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, this measure does not capture indirect associations between nodes. Empirically, the implication of network theory that strength centrality in cross-sectional networks predicts the strength of the association between a symptom's change and the change in the severity of all other symptoms in the network from pre-to post-treatment has received mixed support (Spiller et al, 2020). A fourth limitation is the cross-sectional design, which impairs the ability to draw conclusions about temporal precedence and greater insight into causal direction of the relationships obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Network models of psychopathology posit that highly central nodes (i.e., symptoms) are critical to the course of the disorder since, according to the network perspective, if a central symptom is activated, it is more likely to trigger and influence other symptoms (Borsboom, 2017;McNally, 2016; for a discussion, see Blanchard & Heeren, 2022). And, although the very causal involvement of central nodes in determining the network topology remains to be experimentally proven (for discussion, see Blanchard & Heeren, 2022;Bringmann et al, 2019), early results have confirmed the highly predictive nature of highly central nodes in determining the onset, course, and recovery of psychological disorders (e.g., Boschloo et al, 2016;Elliott, Jones, & Schmidt, 2020;Papini, Rubin, Telch, Smits, & Hien, 2020;Spiller et al, 2020). If this holds true for the models investigated in this study, an intervention that would specifically "turn off" excessive worry should then lead to downstream improvement by rendering the entire network less active.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the relative importance of symptoms in psychopathology networks estimated from observational data, the concept of node centrality was received with high hopes [23]. Centrality indices stem from the domain of social networks, in which the most central node in the network has the largest number of edges with neighboring nodes and the most substantial edges [24].…”
Section: Example Of a Symptom Network Modelmentioning
confidence: 99%
“…The concept was translated to psychology [25], where the centrality hypothesis states that the most central nodes are the best intervention targets, as they are thought to represent the most influential nodes in a network [26]. Therefore, centrality metrices are used in psychopathology networks to identify possible intervention targets [2], [20], [23], [27], [28]. However, several researchers have raised doubts regarding the suitability of centrality indices in psychological networks [23], [29]- [33].…”
Section: Example Of a Symptom Network Modelmentioning
confidence: 99%
See 1 more Smart Citation